PELATIHAN PENGGUNAAN PHET SIMULATION UNTUK MENINGKATKAN KETERAMPILAN IPA CALON GURU SD TAHUN 2024 - Ibrahim; Bahtiar, Bahtiar; Maimun, Maimun; Suranti, Ni Made Yeni; Alimuddin, Nurkhaerat; Wahyuningsih, Baiq Yuni; Hasnawati, Hasnawati (Jurnal Interaktif: Warta Pengabdian Pendidikan, 2024)
Training on the use of PhET Simulation for prospective elementary school teachers in 2024 aims to improve technical and pedagogical skills in teaching science. This training involved a series of planning, introductory, workshop, and evaluation sessions, with a focus on the use of interactive simulations as a learning aid. Evaluation results showed significant improvements in participants' understanding and confidence. Participants also showed greater creativity in designing interactive and interesting learning plans. Despite technical challenges and the need for additional support, it is hoped that this training will improve the quality of science education in Indonesia, motivating students to become more interested and achieve in the field of science. Ongoing support and technological infrastructure improvements are needed to ensure the positive impact of this training continues.